Peramalan harga beras premium di Kabupaten Kebumen - Fitra, Joko; Prasada, Imade Yoga (Agritechpedia, 2024)
Rice prices in Kebumen Regency tend to experience price fluctuations. The same thing also happened to premium IR-64 rice products in Kebumen Regency. The price stabilization scheme needs to be implemented by knowing the price movement patterns of premium rice. Therefore, this research was conducted with the aim of determining the movement pattern of premium rice prices and predicting premium rice prices for the next six months in Kebumen Regency. This research uses secondary data, namely monthly data on premium rice prices in Kebumen Regency in the period August 2015 to June 2024. The data is then analyzed using the ARIMA model. The results of the analysis show that the price of premium rice in Kebumen Regency has a movement pattern that tends to increase from time to time. However, forecasting results show that the price of premium rice in Kebumen Regency will experience a decline in the period July 2024 to December 2024. This is driven by the predicted peak rice harvest season which will take place at the end of 2024